2011
DOI: 10.1007/s00464-011-2095-1
|View full text |Cite
|
Sign up to set email alerts
|

Single-port laparoscopic hepatectomy: technique, safety, and feasibility in a clinical case series

Abstract: The SLH technique is a safe and feasible procedure for a specific group of candidates, including patients with high-grade liver dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 27 publications
2
47
0
2
Order By: Relevance
“…The small case series demonstrated that this technique is feasible in well-selected patients when performed by experienced laparoscopic hepatobiliary surgeons. All previous reports concluded that correct patient selection and laparoscopy experience are the most important part of a successful outcome [10][11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The small case series demonstrated that this technique is feasible in well-selected patients when performed by experienced laparoscopic hepatobiliary surgeons. All previous reports concluded that correct patient selection and laparoscopy experience are the most important part of a successful outcome [10][11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…The indications, contraindications, and technical difficulties such as instrument crowding, absence of triangulation, parallel field of view, and two-to three-instrument restriction depending on the port choice have been discussed in detail in previous reports [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The single-incision laparoscopic method is less invasive than conventional multiport laparoscopy, but there may be unique difficulties for the laparoscopic surgeon. [9][10][11][12][13][14][15] First, retraction is significantly limited. The introduction of a camera and various instruments parallel to each other may result in decreased mobility and the collision of instruments.…”
Section: Discussionmentioning
confidence: 99%
“…El tiempo quirú rgico medio fue de 153 min, similar al descrito en otras publicaciones [18][19][20][21] . El tiempo invertido en la hepatectomía izquierda alarga el tiempo medio empleado en nuestros casos, siendo de 138 min para la seccionectomía lateral izquierda.…”
Section: Discusió Nunclassified
“…La cirugía laparoscó pica por incisió n ú nica se aplicó inicialmente a procedimientos como la colecistectomía 12 y la apendicectomía 13 y posteriormente se ha ido ampliando a otros campos como la cirugía bariá trica, la cirugía de colon o la esplenectomía [14][15][16] . La aplicació n en cirugía hepá tica se reduce hoy en día a publicaciones de series de casos clínicos [17][18][19][20][21] .…”
Section: Introducció Nunclassified